What happens when you stop using the combined contraceptive pill? A qualitative study protocol on consequences and supply needs for women who discontinued the combined contraceptive pill in Germany - Matthias Richter; Liane Schenk; Gertraud Stadler; Jana Niemann (BMJ Open)
Introduction For more than 60 years, contraceptive pills have been prescribed to mostly healthy biological women. An emerging body of research concerning the possible physiological and psychological side effects of hormonal contraception has been published over the past two decades. Consequently, discontinuing combined oral contraceptives (COCs) as a conscious decision for reasons other than desired pregnancy has become increasingly common for menstruating individuals. The question remains as to what physical and psychological consequences can be observed after discontinuing COCs. In addition, the consequent healthcare needs and situations of affected individuals in Germany have not been explored. This study aims to gain greater insight into the relationship between discontinuation of COCs and (1) possible health consequences, and (2) to explore the supply situation for affected women within the German healthcare system.Methods and analysis Qualitative episodic interviews with women who discontinue COC therapy will explore possible health consequences, and their current healthcare needs and situations in Germany. The interviews will be transcribed verbatim, coded, and in-depth thematic interpretation will be conducted. Subsequently, expert interviews with health professionals who work with women who discontinue COCs will also be conducted. The expert interviews will be analysed according to the documentary method. Overarching themes will represent the perspectives of women and health professionals on the discontinuation of COCs.Ethics and dissemination Ethical approval for this study has been granted by the Ethics Review Committee of Martin Luther University, Halle-Wittenberg (Germany), reference number 2021-34. The findings will be disseminated via peer-reviewed publications, posting via social media and presentations at conferences. This study is registered on the OSF platform under the following number: https://doi.org/10.17605/OSF.IO/JYWXM.